1996
DOI: 10.1021/om960123l
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Stoichiometric Alkyne Insertion into Pt−B Bonds and Related Chemistry Bearing on the Catalytic Diborylation of Alkynes Mediated by Platinum(II) Diboryl Complexes

Abstract: The insertion reactivity of alkynes with the diboryl complex (Ph 3 P) 2 Pt(BCat) 2 (1, Cat ≡ {C 6 H 4 O 2 } 2-) has been investigated. Under stoichiometric conditions 1 mediates cisdiborylation of alkynes and the (PPh 3 ) 2 Pt fragment is trapped by alkyne to give the corresponding Pt-alkyne complexes. Kinetic studies under pseudo first-order conditions of alkyne indicate that the reaction is first order in 1. In the absence of added phosphine, no alkyne dependence is observed. The stoichiometric reaction is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
90
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(105 citation statements)
references
References 57 publications
13
90
1
1
Order By: Relevance
“…Kinetic investigations revealed that the process was firstorder overall in concentration of the platinumbisboryl species. 29 A number of alkynes 25,26,29,30 and diynes 30 43 In addition, a detailed examination of the alkyne diboration reaction was also reported 42 which showed that insertion of acetylene into the Pt-B(OH) 2 bond was exothermic by 28.1 kcal mol -1 with the overall reaction being exothermic by 60.8 kcal mol -1 . With the rate-determining step in the catalysis calculated to be phosphine dissociation from [Pt(PH 3 42 it is not surprising that the insertion proceeds readily when a monophosphine catalyst was prepared using [Pt(cod) 2 ].…”
Section: Reactions With H 2 and Omentioning
confidence: 98%
See 1 more Smart Citation
“…Kinetic investigations revealed that the process was firstorder overall in concentration of the platinumbisboryl species. 29 A number of alkynes 25,26,29,30 and diynes 30 43 In addition, a detailed examination of the alkyne diboration reaction was also reported 42 which showed that insertion of acetylene into the Pt-B(OH) 2 bond was exothermic by 28.1 kcal mol -1 with the overall reaction being exothermic by 60.8 kcal mol -1 . With the rate-determining step in the catalysis calculated to be phosphine dissociation from [Pt(PH 3 42 it is not surprising that the insertion proceeds readily when a monophosphine catalyst was prepared using [Pt(cod) 2 ].…”
Section: Reactions With H 2 and Omentioning
confidence: 98%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37] In addition, related theoretical studies regarding M-B bond energies of metal-boryl compounds and the mapping of reaction coordinates for the proposed catalytic cycles have also been reported. [38][39][40][41][42][43][44] Initially, Nöth and Schmid examined four general synthetic routes for the preparation of metal-boryl compounds, namely: (i) the nucleophilic reaction of anionic metal species with haloboranes (X-BR 2 , X ) Cl, Br, I), (ii) the reaction of metal hydride compounds with haloboranes, (iii) σ-bond metathesis reactions with cobalt bisboryl compounds, and (iv) oxidative addition of haloboranes by metal compounds.…”
Section: Introductionmentioning
confidence: 99%
“…1-18 These complexes have been invoked as intermediates in a number of catalytic systems including metal-catalyzed hydroboration of unsaturated substrates and diboration of alkynes, alkenes, dienes, and allenes. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Although theoretical studies regarding metal-boryl bond energies and the mapping of the reaction coordinate for the proposed catalytic cycles have been reported, 35-42 accurate theoretical investigations which address the nature of the chemical bond (1) Wadepohl, H. Lawlor, F. J.; Marder, T. B.; Nguyen, P.; Norman, N. C.; Orpen, A. G.; Quayle, M. J.; Rice, C. R.; Robins, E. G.; Scitt, A. J.; Souze, F. E. S.; Stringer, G.; Whittell, G. R. Johann, T.; Marder, T. B.; Norman, N. C.; Orpen, A. G.; Peskman, T.; Quayle, M. J.; Rice, C. R.; Scott, A. J. …”
mentioning
confidence: 99%
“…The slow reaction of 2 having strong electron-donating groups (Entries 7 and 8) may reflect the rate of insertion step, which was consistent with the relative reactivity observed on the insertion of diarylacetylenes to the B-Pt bond. 10 The selective formation of 3a in the reaction of 1,1-disubstituted 2 may be due to the steric requirement; however, the observed regio-and stereoselectivity for monosubstituted and heteroatom-substituted 2 remains controversial. The ready availability of various 3 from 2 now offers a simple route to substituted homoallyl alcohols.…”
mentioning
confidence: 99%